Strengthening Students’ Digital Competence through a Holistic Learning Model Based on Local Wisdom: An Authentic Assessment-Based Evaluation - Ari Hasan Ansori; Didih Muhamad Sudi (Attractive : Innovative Education Journal, 2026)
The digital transformation in education necessitates that students possess not only technical skills but also culturally grounded and ethically informed digital competencies. This study investigates the effectiveness of a holistic learning model rooted in local wisdom in enhancing the digital competencies of students at STAI Syekh Manshur, employing authentic assessment as a key evaluative mechanism. Utilizing a mixed-methods embedded design, the research integrates quantitative analyses—including pre–post tests and authentic assessments—with qualitative insights derived from interviews and classroom observations. A total of 80 students participated in the study. Findings reveal statistically significant improvements across all dimensions of DigComp 2.2—Information and Data Literacy, Communication and Collaboration, Digital Content Creation, Safety, and Problem Solving (p < 0.001)—with very large effect sizes. Authentic assessment further demonstrated that students’ digital performance ranged from high to very high. Qualitative evidence underscores that embedding local wisdom values—such as mutual cooperation (gotong royong), deliberation (musyawarah), trustworthiness (amanah), and virtuous character (akhlāq al-karīmah)—substantially contributes to the enhancement of critical awareness, digital ethics, creativity, and problem-solving abilities. Overall, the holistic learning model grounded in local wisdom proves effective in comprehensively strengthening students’ digital competencies and holds considerable relevance for implementation in Islamic higher education institutions.